Comparison of sales force trainings in tractor industry - P. RADHIKA, VIVEK SINGH AND (The Journal of Research, PJTSAU, 2017)
Agricultural machinery industry is an important segment of the agribusiness sector and in India farm mechanization has played a significant role in taking out the country from starvation situation (after independence) to a self-sufficiency position and because of mechanization, motive (tractor) andstationary (diesel and electric motor) power are in command over animate power since 1980-81.India’s tractor industry is the largest in the world andcontributes around 33 per cent to the global production. During 2003, the tractor density in India was 12 tractors per 1000 hectares of Gross cropped area compared with world average of above 50.Farm mechanization has led to the increase in gross cultivated area (from 165.8 M ha in 1970-71 to 193.8M ha in year 2007-08), cropping intensity (from 118 per cent in year 1970-71 to 137.2 per cent in year 2007-08) and yield (productivity based on net sownarea increased from 0.872 t/ha in year 1970-71 to 1.854 t/ha in year 2007-08) in addition to employment (Singh et al., 2009). The sales volume growth of tractor industry in the past two decades shows a Compound Annual Growth Rate (CAGR) of 5.81 per cent, despite seasonal variations that cause natural fluctuations in the demand of tractors (Bhalla, 2010).There are currently 13 national and few regional players in tractor manufacturing, Mahindra & Mahindra being the leading manufacturer. Other major players are TAFE (Massey Ferguson and Eicher), International Tractors Limited (Sonalika), Punjab Tractors Limited (PTL), Escorts, John Deere, New Holland India, Hindustan Machine Tools (HMT), Force mo tors, Mahindra Gujarat Tractors Limited. However the market share is concentrated amongst the top five manufactures Mahindra & Mahindra, TAFE, Escorts, John Deere, and Sonalika.